Transmission properties of acousto optic material - Saidin, Mohamad Khairi; Mat Daud, Nazariah; Bidin, Noriah; Mat Daud, Yaacob (Laser Technology Laboratory, Physics Department Faculty of Science, University Teknologi Malaysia, 2007)
Laser beam can be modulated by acousto optic modulator using a suitable acousto optic material. UV-VIS Spectrophotometer was utilized to investigate the transmission spectrum of two non linear acousto optic materials that are lithium niobate and fused quartz. From the spectrum it shows that transmittance for fused quartz and lithium niobate were 90% and 68% respectively. The absorption coefficient ? is calculated and plotted versus photon energy. It was found that ? increases linearly with photon energy in the range of 3.50 eV to 4.0 eV for fused quartz and 3.15 eV to 4.0 eV for lithium niobate. The estimated optical energy band gap was 2.97 eV for lithium niobate and 3.69 for fused quartz. From the transmission properties obtained in this study, it can be summarized that fused quartz is a better choice to be an acousto optic material.